Mapping of P-Available Content, P-Total and Cadmium in Paddy Fields of Pematang Nibung Village Medang Deras District, Batu Bara Regency - imelda pakpahan; hardy guchi; jamilah jamilah (Jurnal Agroekoteknologi, 2019)
This study aims to map P-Available, P-Total and Cadmium in paddy fields of Pematang Nibung Village, Medang Deras Subdistrict, Batu Bara District, with 109 ha of paddy fields area. This Study  carried out from March to August 2018. The method used in this research was grid survey method that observe the soil are carried out in regular pattern (the interval of observation points is equidistant in the vertical and horizontal directions). So that there are 14 points of 450 m longitude and latitude, analyzed its P-Available nutrient data (ppm) using Bray II  method  with spectrophotometer, P-Total (%) by using HNO3 extraction method with  spectrophotometer and Cadmium (ppm) by using AAS (Atomic  Absorbtion  Spectrophotometer) and interpolated it on maps with QGIS software and correlation analysis with Microsoft Excel. The results showed the distribution of  high  P-Available (53.39-159.06 ppm) nutrient status hara was as much as 109 ha (100 %). Distribution of Medium P-Total (0.06-0.07 %) nutrient status was as much as 26,87 ha (24.65 %), and rather high P-Total (0.09-0.10 %) was as much as 21.87ha (20.06 %), and high P-Total (0.11-0.13 %) was as much as 60.26 ha (55.28 %). Distribution of (0.01-0.05 ppm) uncontaminated Cadmium was as much as 109 ha (100 %). The analysis of P-Available correlation coefficient value was very weak related and not significant for P-Total which is 0.90. The analysis of P-Available correlation coefficient value is weak related and not significant for Cadmium which is -0.32. The analysis of P-Total correlation coefficient value was very weak related and not significant for Cadmium which is 0.10.